Pengembangan Kapasitas Aparatur Desa Dalam Menuju Desa Digital di Desa Doulan Kecamatan Bokat Kabupaten Buol - U.Timumun, Rahmat Hidayat; Tui, Fenti Prihatini Dance; Tohopi, Rustam (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze and describe the capacity development of village officials towards a digital village in Doulan Village, Bokat District, Buol Regency as seen from: Joint Committee, Education, Knowledge, Leadership and Skills. This research method uses a descriptive approach with qualitative data analysis. The data collection techniques used are observation, interviews, documentation. The data analysis technique goes through the following stages: Data Reduction, Data Presentation and Data Verification. Based on the results of research analyzed in the field, the capacity development of village officials towards a digital village in Doulan Village, Bokat District, Buol Regency is seen from: Joint Committee, Education, Knowledge, Leadership and Skills. It has been implemented well, but there are still several things that need to be addressed and improved, namely the lack of knowledge regarding village digital. The need for technical guidance which is often provided by the local government. As well as increasing network capacity or signals used when inputting data.